Design And Proportional Computational Assessment Rectangular Duct Air Conditioning System At Shopping Mall - Muhammad Nur Alif,; Sies, Ts. Dr. Mohamad Farid (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Ducting is essential in the HVAC system as it functions as a conduit to supply cooled air into the room. However, there are some problems with a long ducting system, especially in a big building like a shopping mall, where there are losses along the ductworks. So, suitable ducting needs to be designed for better performance. At the same time, effective in terms of cost. This study aims to develop a practical design for a rectangular duct system at a shopping mall using CFD analysis. In this study, we use both theoretical results based on manual calculation and numerical solutions using CFD analysis. Three methods of designing the ducting system are applied: equal friction, velocity reduction, and static regain. This study can compare and discuss the result of these three methods. Based on the result, the static regains method produce a better ducting system in term of performance and cost because it produces the highest velocity at the last outlet. Therefore, an excellent ducting system needs to be designed for better HVAC system performance.